A Corpus‐based Psychodynamic Analysis of Body Boundary Imagery in Hitler's Mein Kampf. (30th July 2013) - Cariola, Laura A.
ABSTRACT This study employs a corpus‐based approach to make justifiable psychodynamic interpretations based on the statistical relationships that exist between linguistic variables in written texts. The text examined is Hitler's Mein Kampf (Boston, MA: Houghton Mifflin, 1943), which was assessed on the strengths of associations between body boundary imagery, primordial thought language and emotional language. The results largely confirm the research hypotheses identifying the use of body boundary functions as a defense mechanism associated to borderline and narcissistic organization for separating trauma from conscious awareness and for containing a fragile self‐image and body schema. The discussion interprets the language pattern by drawing on various psychoanalytic theories in conjunction with Hitler's biographical notes and Langer's psychohistorical study of Hitler's life (The mind of Adolf Hitler: The secret wartime report. London: Pan, 1973). Copyright © 2013 John Wiley & Sons, Ltd.